Cardiometabolic and psychological effects of dual-release hydrocortisone: a cross-over study. Issue 2 (February 2021) - Dineen, Rosemary; Martin-Grace, Julie; Ahmed, Khalid Mohamed Saeed; Frizelle, Isolda; Gunness, Anjuli; Garrahy, Aoife; Hannon, Anne Marie; O'Reilly, Michael W; Smith, Diarmuid; McDermott, John; Healy, Marie-Louise; Agha, Amar; et al.
Abstract : Background: Adrenal insufficiency (AI) is associated with increased cardiovascular morbidity and mortality and reduced quality of life (QoL). Optimum glucocorticoid (GC) dosing and timing are crucial in the treatment of AI, yet the natural circadian secretion of cortisol is difficult to mimic. The once-daily dual-release hydrocortisone (DR-HC) preparation (Plenadren®), offers a more physiological cortisol profile and may address unmet needs. Methods: An investigator-initiated, prospective, cross-over study in patients with AI. Following baseline assessment of cardiometabolic risk factors and QoL, patients switched from their usual hydrocortisone regimen to a once-daily dose equivalent of DR-HC and were reassessed after 12 weeks of treatment. Results: Fifty-one patients (21 PAI/30 SAI) completed the study. Mean age was 41.6 years (s.d. 13), and 58% ( n = 30) were male. The median daily HC dose before study entry was 20 mg (IQR 15–20 mg). After 3 months on DR-HC, the mean SBP decreased by 5.7 mmHg, P = 0.0019 and DBP decreased by 4.5 mmHg, P = 0.0011. There was also a significant reduction in mean body weight (−1.23 kg, P = 0.006) and BMI (−0.3 kg/m 2, P = 0.003). In a sub-analysis, there was a greater reduction in SBP observed in patients with SAI when compared to PAI post-DR-HC. Patients reported significant improvements in QoL using three validated QoL questionnaires, with a greater improvement in PAI. Conclusion: Dual-release hydrocortisone decreases BP, weight and BMI compared with conventional HC treatment, even at physiological GC replacement doses. Additionally, DR-HC confers significant improvements in QoL compared to immediate-release HC, particularly in patients with PAI, which is also reflected in the patient preference for DR-HC.